Urolithiasis: Comprehensive Review of Etiology, Diagnosis and Treatment - Kaźmierczak, Jakub; Bartosiński, Ryszard; Szustak, Jan; Wijata, Anna; Przybyłek- Stępień, Zuzanna Adriana; Dutkiewicz, Justyna; Mączyńska, Wiktoria; Kąpa, Maria; Szepietowski, Bartosz; Wijata, Michał; Rycerz, Ewelina; Pasek, Piotr (Quality in Sport, 2025)
Urolithiasis, commonly referred to as kidney stone disease, is a prevalent and recurrent urological condition with significant global health and economic implications. The formation of urinary calculi results from a multifactorial interplay between genetic predisposition, metabolic abnormalities, dietary habits, and environmental factors. The incidence of urolithiasis has been rising worldwide, particularly in developed countries, contributing to an increasing burden on healthcare systems. This review provides a comprehensive analysis of the etiology and risk factors associated with kidney stone formation, including dietary and non-dietary contributors such as high animal protein intake, calcium and oxalate metabolism, obesity, diabetes, and climate influences. Advances in diagnostic modalities, particularly the role of non-contrast computed tomography (CT), ultrasonography, and metabolic evaluation, have improved early detection and classification of urinary stones. Treatment options range from conservative medical management to surgical interventions, including extracorporeal shock wave lithotripsy (ESWL), ureteroscopy (URS), and percutaneous nephrolithotomy (PCNL), with evolving techniques enhancing stone clearance and minimizing recurrence. Furthermore, lifestyle modifications, adequate hydration, and pharmacological interventions play crucial roles in the prevention of recurrent stone formation. The growing prevalence of urolithiasis underscores the need for continuous advancements in both preventive and therapeutic strategies. Further research into stone pathophysiology, metabolic risk assessment, and novel treatment modalities is essential to reduce morbidity and healthcare costs associated with this condition.